Sosialisasi konsep penyakit Diabetes Mellitus untuk meningkatkan pengetahuan Lansia tentang Diabetes Mellitus - Purqoti, Dewi Nur Sukma; Arifin, Zaenal; Istiana, Dian; Ilham, Ilham; Fatmawati, Baiq Ruli; Rusiana, Harlina Putri (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Diabetes Mellitus (DM) is one of the degenerative diseases known as a lifelong disease because it is a disease that cannot be cured during the life span of the sufferer and is commonly found in the elderly. In the management of DM, six things must be considered, including education, dietary regulation, regular physical activity, medicaments, insulin use, and monitoring daily blood sugar levels. The purpose of this community service activity is to increase the knowledge of the elderly about the basic concepts of DM. The method of community service activities was carried out by providing health education about the basic concepts of DM and its handling through lectures and questions and answers. The stages of the activity start from measuring residents' knowledge about DM as pre-test data, then giving material on the basic concepts of DM and its handling through lectures and subsequent sessions of question and answer about material that is not yet clear. The last stage is to re-measure citizens' knowledge about the concept of DM as post-test data. This activity results in an increase in knowledge after being given Health Education. This community service activity concludes that the socialization of the concept of DM disease has a positive impact on the knowledge of the elderly about DM. Similar activities must continue to be carried out to improve the quality of life of people with DM.